Peran Mahasiwa Kuliah Kerja Nyata (KKN) dalam Integrasi Digital Marketing : Strategi Pemberdayaan Masyarakat Berkelanjutan Desa Sadangmekar Kecamatan Cisarua Kabupaten Bandung Barat: Pengabdian - Ciptadi Ramadan Saefullah Sudrajat; Aldila Nuur Alisa Maharani; Afiyfah Faidz; Ikmal Bani Ibrahim; Najwa Haqqi Salma; Dini Nurhandayani; Vinki Azhari Pangestika Ma’ruf; Syifa Nur Ilahiyah; Bhunga Shazkia Illahi; Rama; Dian Kusumawati (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The Community Service Program (KKN) is one form of student service to society, implemented as part of the Tri Dharma of Higher Education. This activity aims to empower communities, particularly in the field of education, by applying the knowledge acquired during their academic studies. This research focuses on the role of KKN students in improving the quality of education in Citorondool Village, Sarimukti, Pasirwangi District, Garut Regency. Citorondool Village is one of the areas facing challenges in providing quality education, primarily due to limited access and adequate facilities. Through the KKN program, students strive to contribute by organizing activities such as tutoring, educational outreach, and introducing technology to students and the community. The research findings indicate that KKN students significantly enhance students' learning motivation and broaden the community’s awareness of the importance of education.